A Comparison of the Impact of Protective and Preservative Video Surveillance on Urban Territoriality: the case of Switzerland - Klauser, Francisco (My University, 2004)
The paper compares the socio-spatial logics and implications of two ideal-typical forms of CCTV: (1) preservative CCTV, which aims to preserve public order and to prevent ‘antisocial’ behaviour; and (2) protective CCTV, which aims at monitoring specific risk-points, buildings or objects. This investigation is based on the cartographical study of the spatial distribution of CCTV within the city centre of Geneva and a study of the public perception of video surveillance in the Swiss city of Olten.